Calculation of the effect of tip geometry on noncontact atomic force microscopy using a qPlus sensor - Stirling, Julian; Shaw, Gordon A. (Beilstein Journal of Nanotechnology, 2013)
In qPlus atomic force microscopy the tip length can in principle approach the length of the cantilever. We present a detailed mathematical model of the effects this has on the dynamic properties of the qPlus sensor. The resulting, experimentally confirmed motion of the tip apex is shown to have a large lateral component, raising interesting questions for both calibration and force-spectroscopy measurements.
Keywords: atomic force microscopy; force spectroscopy; lateral forces; mechanical vibrations; qPlus

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Giessibl, F. J.; Hembacher, S.; Bielefeldt, H.; Mannhart, J. (Science, 2000)

(untitled) - Ternes, M.; Lutz, C. P.; Hirjibehedin, C. F.; Giessibl, F. J.; Heinrich, A. J. (Science, 2008)

(untitled) - Sweetman, A.; Jarvis, S.; Danza, R.; Bamidele, J.; Gangopadhyay, S.; Shaw, G. A.; Kantorovich, L.; Moriarty, P. (Phys. Rev. Lett., 2011)

(untitled) - Sweetman, A.; Jarvis, S.; Danza, R.; Bamidele, J.; Kantorovich, L.; Moriarty, P. (Phys. Rev. B, 2011)

(untitled) - Chiutu, C.; Stannard, A.; Sweetman, A. M.; Moriarty, P. (Chem. Commun., 2011)

(untitled) - Chiutu, C.; Sweetman, A. M.; Lakin, A. J.; Stannard, A.; Jarvis, S.; Kantorovich, L.; Dunn, J. L.; Moriarty, P. (Phys. Rev. Lett., 2012)

(untitled) - Sweetman, A.; Jarvis, S.; Danza, R.; Moriarty, P. (Beilstein J. Nanotechnol., 2012)

(untitled) - Giessibl, F. J. (Rev. Mod. Phys., 2003)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 2000)

(untitled) - Tung, R. C.; Wutscher, T.; Martinez-Martin, D.; Reifenberger, R. G.; Giessibl, F.; Raman, A. (J. Appl. Phys., 2010)

(untitled) - Sader, J. E.; Jarvis, S. P. (Appl. Phys. Lett., 2004)

MEMS and Nanotechnology, Volume 2 - Shaw, G. A.; Pratt, J. R.; Jabbour, Z. J. (Small mass measurements for tuning fork-based atomic force microscope cantilever spring constant calibration, 2011)

(untitled) - Heyde, M.; Kulawik, M.; Rust, H.-P.; Freund, H.-J. (Rev. Sci. Instrum., 2004)

(untitled) - Giessibl, F. J. (Phys. Rev. B, 1997)

Mechanical vibrations - Rao, S. (Addison-Wesley, 1995)

(untitled) - Butt, H.-J.; Jaschke, M. (Nanotechnology, 1995)

(untitled) - Nowakowski, B. K.; Smith, S. T.; Pratt, J. R.; Shaw, G. A. (Rev. Sci. Instrum., 2012)

(untitled) - Lozano, J. R.; Kiracofe, D.; Melcher, J.; Garcia, R.; Raman, A. (Nanotechnology, 2010)